Safety and immunogenicity of COVID‐19 vaccination in patients with hepatocellular carcinoma (CHESS‐NMCID 2101): A multicenter prospective study. Issue 11 (26th July 2022) - Qi, Xiaolong; Wang, Jitao; Zhang, Qiran; Ai, Jingwen; Liu, Chuan; Li, Qianqian; Gu, Ye; Lv, Jiaojian; Huang, Yifei; Liu, Yanna; Xu, Dan; Chen, Shubo; et al.
Abstract: Data on safety and immunogenicity of coronavirus disease 2019 (COVID‐19) vaccinations in hepatocellular carcinoma (HCC) patients are limited. In this multicenter prospective study, HCC patients received two doses of inactivated whole‐virion COVID‐19 vaccines. The safety and neutralizing antibody were monitored. Totally, 74 patients were enrolled from 10 centers in China, and 37 (50.0%), 25 (33.8%), and 12 (16.2%) received the CoronaVac, BBIBP‐CorV, and WIBP‐CorV, respectively. The vaccines were well tolerated, where pain at the injection site (6.8% [5/74]) and anorexia (2.7% [2/74]) were the most frequent local and systemic adverse events. The median level of neutralizing antibody was 13.5 (interquartile range [IQR]: 6.9–23.2) AU/ml at 45 (IQR: 19–72) days after the second dose of vaccinations, and 60.8% (45/74) of patients had positive neutralizing antibody. Additionally, lower γ‐glutamyl transpeptidase level was related to positive neutralizing antibody (odds ratio = 1.022 [1.003–1.049], p = 0.049). In conclusion, this study found that inactivated COVID‐19 vaccinations are safe and the immunogenicity is acceptable or hyporesponsive in patients with HCC. Given that the potential benefits may outweigh the risks and the continuing emergences of novel severe acute respiratory syndrome coronavirus 2 variants, we suggest HCC patients to be vaccinated against COVID‐19. Future validation studies are warranted.